On the "Teaching of Philosophy" and Touristic Education: Commitments and Responsibilities - Villalobos Paniagua, Ricardo Antonio (2021)
A piece of writing is intended which relates tourism, as a profession, to philosophy and education, appreciating the role of the touristologist, and in this way, transcending the character of the tourist who, commonly, takes pleasure in his or her egocentric intentions to produce an ephemeral and solipsistic pleasure (“solus ipse”), with the danger of opting for indifference, even, of what happens around him or her as an extension of consumerism and materialism. Still, and despite the fact that attempts have been made to generate responsible tourism committed to the cultural environment, ecology, and the legacy of historical heritage, this essay shows an ideal understood as a personal goal and with a pedagogical and ethical objective. This appreciation stems from the author’s existential, work, and academic experience, the ultimate goal of which is to denote a constant need to ethically interpret tourism, being itself a potential pedagogical path, rather than simply one aimed at leisure.